1997
DOI: 10.1046/j.1365-2249.1997.4941392.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 production by allergen-stimulated T cells following grass pollen immunotherapy for seasonal allergic rhinitis

Abstract: SUMMARYGrass pollen immunotherapy for the treatment of seasonal allergic rhinitis ('summer hayfever') results in improvement in symptoms, a reduction in the early and late phase responses to allergen provocation and decreased tissue eosinophilia. Immunotherapy may act by altering the pattern of cytokine production by allergen-specific T cells from a 'Th2-type' (IL-4 and IL-5) profile to a 'Th1-type' (interferon-gamma (IFN-g)) profile. We set out to determine whether clinical improvement following specific alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
2
10
1
1
Order By: Relevance
“…Other investigators have reported a decrease in Th2 cytokine production in favour of Th1 cytokines such as IFN‐γ by peripheral blood T cells in response to allergen 30 . In contrast, our own cross‐sectional studies did not identify a significant difference in peripheral T‐cell responsiveness to allergen or IL‐5 production in patients who had received immunotherapy compared to placebo‐treated patients 31 . In the present study we performed a further prospective randomized controlled trial of grass pollen immunotherapy in patients with severe hayfever.…”
Section: Introductioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Other investigators have reported a decrease in Th2 cytokine production in favour of Th1 cytokines such as IFN‐γ by peripheral blood T cells in response to allergen 30 . In contrast, our own cross‐sectional studies did not identify a significant difference in peripheral T‐cell responsiveness to allergen or IL‐5 production in patients who had received immunotherapy compared to placebo‐treated patients 31 . In the present study we performed a further prospective randomized controlled trial of grass pollen immunotherapy in patients with severe hayfever.…”
Section: Introductioncontrasting
confidence: 94%
“…In addition to the findings reported here, a number of other studies have reported a lack of effect of clinically successful pollen immunotherapy on peripheral blood T‐cell responses 35–37 . Our own cross‐sectional studies of peripheral blood T‐cell responses after 4–7 years of clinically effective immunotherapy 38 did not show any evidence for reduction in grass pollen‐induced proliferation or IL‐5 production 31 . This is unlikely to be explained by methodological differences since using identical methodology previously we demonstrated a close correlation between in vitro cytokine production for IL‐5 in PBMC cultures and the clinical severity of allergic disease expression 15 .…”
Section: Discussionsupporting
confidence: 63%
“…At the beginning of the 1990s, with the definition of the Th1–Th2 paradigm, initial results based on several in vitro and in vivo models concluded that SCIT skewed allergen‐specific responses from Th2 to a more protective Th1 phenotype, a mechanism known as immunodeviation [9,40]. Others have been unable to reproduce these findings, and reported no changes in proliferative responses or cytokine production [41], due probably to variations of SCIT regimens and in vitro methodology. Nevertheless, Th1‐redirection induced by SCIT with allergen extracts or peptides continues to be reported in more recent studies [42–44].…”
Section: Certainties and Controversies Of T Cell Response During Scitmentioning
confidence: 99%
“…Immunotherapy to divert the T cell cytokine response from a type 2 to a type 1 profile should therefore prevent the allergic response to antigen. A number of studies have found that conventional allergen immunotherapy causes a reduction in T cell synthesis of IL‐4, but effects on type 1 and other type 2 cytokines are variable and the underlying mechanisms are not understood 190 , 191 , 192 …”
Section: Therapeutic Exploitation Of the Cytokine Networkmentioning
confidence: 99%